Out-of-hospital assessment and management of rape survivors by pre-hospital emergency care providers in the Western Cape - Gihwala, Raina Tara (Division of Emergency Medicine, 2016)
South African incidence of rape ranks amongst the highest worldwide. No direct policy exists for the emergency care provider management of rape victims in the pre-hospital setting. The pre-hospital exposure to rape cases is unknown as its health information system is not gender-based violence sensitive. In the absence of a clearly defined protocol, indiscretion in the emergency care treatment of rape victims remains undocumented. As a particularly vulnerable group globally, victims of rape are deserving of focused intervention. A qualitative, descriptive approach guided the research in which nine semi-structured voluntary interviews were held with emergency care providers, forensic medical practitioners and emergency consultants. Through a critical theory lens thematic content analysis was employed. University of Cape Town ethics approval was attained. The study found that pre-hospital providers lack knowledge and skills of rape victim identification and management but are desirous of evidence-informed guidelines for treatment and referral in a multidisciplinary approach. Educational and policy deficiencies are documented. The recommendations support a community of practice that is mutually inclusive of specialist rape-care centres, emergency department and pre-hospital providers in the interest of forensic emergency medicine. Due regard must be had for needs of practitioners at risk of vicarious traumatization from sexual assault management. Transformative curricula and responsive clinical guidelines are likely to redress any complicity of the health sector non-response to rape/sexual assault. This study is likely to benefit emergency care regulators, educators and researchers whose professional interest is to promote responsivity of the health system to rape.